Exploration of Teaching Methodology in a Medical College, Rawalpindi: A Qualitative Assessment from Students’ Perspective - Tariq, Naseer Alam; Shah, Amna Yousaf; Jafri, Adeel Ahmed; Bajwa, Azka Aslam (Pakistan Armed Forces Medical Journal, 2024)
Objective: To explore how to improve teaching methodology in a medical college from students’ perspective.Study Design: Qualitative grounded theory study design using constructivist approach.Place and Duration of Study: Conducted at public sector medical college of three-months duration from Dec 2016 to Mar 2017.Methodology: A grounded theory approach was used explore student’s perspective of how to improve teaching methodologies. Two focus group discussion of 4th and final year MBBS students were conducted. Data were collected on semi-structured questionnaire and analyzed manually by thematic analysis.Results: There were five main themes which are as follows: Teaching techniques, students’ assessment, and clinical rotation, extra-curricular and future prospects. In teaching techniques further 4 sub-themes emerged i.e. lectures, slides, courses and attendance. In student assessment further four sub-themes emerged as exams, practicals, viva and CBLS. In clinical rotations, three sub-themes emerged as ward rounds, surgical operations and timings. In extracurricular activities, three sub-themes emerged as sports, workshops and research. In future prospects only two sub-themes emerged as alumni and affiliations. All of the sub-themes had the problem narrated with their suggestive solutions. For example; in teaching techniques the suggestions were decreasing duration of lectures, breaks in-between lectures and lecture being more interactive.Conclusion: The teaching methodology lacks a practical approach regarding medical studies along with lack of student- teacher interaction. Students should be asked to give active feedback regarding any changes that they would want; this would not only help break down the barrier between students and teachers but also all